Analisa Kualitas Layanan Pada E-learning di Sekolah Menggunakan Metode Servqual - Tri Sentia; Mustafia Mustafia; Eva Zuraidah (Journal of Informatics Management and Information Technology, 2022)
Service quality is the main thing that users of e-learning applications always hope to receive, and these virtues are used to meet the expectations of users. The problem that occurs is that the quality of service is still lacking in the service order, causing the e-learning application to be unable to be reopened. Students who are late in submitting assignments must enter manually and the answers cannot be tracked. The purpose of this study was to measure the quality of service that affects the level of user satisfaction with the servqual method. Measurement of satisfaction for users in measuring the level of satisfaction with 5 dimensions of service quality, namely Tangible, Reliability, Responsiviness, Assurance, and Empathy. The result of the gap between perceptions and expectations of users is -0.08. The gaps are grouped based on attributes using an IPA (Importance Performance Analysis) diagram with the Tangible dimension, the value of the gap is -0.09, the attributes of e-learning application services must be maintained by users who always wear clear student ID cards so that they can be known. Reliability with a gap of -0.07, covering website context related to school e-learning, and guidebooks according to website content. Responsiveness with a gap value of -0.10, namely the attendance menu on the website is functioning properly, notifications appear when there is new information. Assurance with a gap of -0.10, guaranteed website security, and easy to file a complaint if there are website problems. And Empathy with a gap value of -0.08 for convenience in using the website, easy contact, and good communication with supervisors.